Lower limb injuries in an English professional football club: injury analysis and recommendations for prevention - Fares, M. Y.; Stewart, K.; McBride, M.; Maclean, J. (The Physician and Sportsmedicine, 2023)
Background Lower limb injuries constitute a problem in the sport of football. Our aim is to explore patterns and trends of lower limb injuries in an English professional football club.